CW-EPR studies revealed different motional properties and oligomeric states of the integrin β(1a) transmembrane domain in detergent micelles or liposomes - Yu, Lu (Sci Rep, 2015)
Integrins are heterodimeric membrane proteins that regulate essential processes: cell migration, cell growth, extracellular matrix assembly and tumor metastasis. Each integrin α or β subunit contains a large extracellular domain, a single transmembrane (TM) domain, and a short cytoplasmic tail. The integrin TM domains are important for heterodimeric association and dissociation during the conversion from inactive to active states. Moreover, integrin clustering occurs by homo-oligomeric interactions between the TM helices. Here, the transmembrane and cytoplasmic (TMC) domains of integrin β(1a) were overexpressed, and the protein was purified in detergent micelles and/or reconstituted in liposomes. To investigate the TM domain conformational properties of integrin β(1a), 26 consecutive single cysteine mutants were generated for site-directed spin labeling and continuous-wave electron paramagnetic resonance (CW-EPR) mobility and accessibility analyses. The mobility analysis identified two integrin β(1a)-TM regions with different motional properties in micelles and a non-continuous integrin β(1a)-TM helix with high immobility in liposomes. The accessibility analysis verified the TM range (Val737-Lys752) of the integrin β(1a)-TMC in micelles. Further mobility and accessibility comparisons of the integrin β(1a)-TMC domains in micelles or liposomes identified distinctively different oligomeric states of integrin β(1a)-TM, namely a monomer embedded in detergent micelles and leucine-zipper-like homo-oligomeric clusters in liposomes.